Theoretical -Methodological Review of the General Education Management Models - Gasparyan, Mkhitar (ՀՀ ԳԱԱ)
Management of the general education system is a theoretical and practical area of social sciences aimed at developing a strategy for the education system, planning and monitoring educational processes, identifying current management tasks, and solving them effectively. Management of general education has become an integral part of the educational system as a whole since the organization and implementation of educational processes are impossible without the use of management mechanisms and skills. Moreover, the area of general education management has become a kind of link between the academic needs of society and the strategic goals of the state. Therefore, management of the general education system is not only an area of theoretical knowledge but also has great practical and social significance. Along with the achievements of scientific thought in the field of general education management, it should be noted that the rapid development of modern societies requires periodic revision of theoretical management models and their compliance with the current educational needs of society. Modern social demands and expectations regarding the educational system dictate the need to develop criteria for selecting a management model. Today, such issues have already emerged in the field of general education management, of which the following issues are of particular importance: - the presence of various management models in practice and the absence of their theoretical description; - formal choice of management models for educational systems; - contradictions between multiple changes in the education system and the lack of theoretically sound models for managing these changes. To formulate theoretical and practical recommendations aimed at solving of current problems in the area of general education management there were investigated trends of management models formed and their essential characteristics. The objectives of this study include describing the main characteristics of social connections that form configurations of relationships between general schools and society and constructing a typology of management models that dominate modern schools of various countries. These objectives were formed based on qualitative data obtained during a comparative study of international experience in the field of general education management. Հանրակրթության ոլորտի կառավարումը սոցիալական գիտությունների տեսական և գործնական ոլորտ է, որն ուղղված է կրթական համակարգի ռազմավարության մշակմանը, կրթական գործընթացների պլանավորմանն ու մոնիթորինգին, ընթացիկ կառավարման խնդիրների բացահայտմանը և դրանց արդյունավետ լուծմանը: Հանրակրթության ոլորտի կառավարումը դարձել է կրթական համակարգի անբաժանելի մասը, քանի որ կրթական գործընթացների կազմակերպումն ու իրականացումն անհնար է առանց կառավարման մեխանիզմների և հմտությունների կիրառման: Ավելին, հանրակրթության կառավարման ոլորտը դարձել է հասարակության կրթական կարիքների և պետության ռազմավարական նպատակների միջև կապող օղակը, ուստի՝ հանրակրթության ոլորտի կառավարումը ոչ միայն տեսական գիտելիքի ձևավորման ոլորտ է, այլև ունի գործնական և սոցիալական մեծ նշանակություն ։ Հանրակրթության կառավարման ոլորտում գիտական մտքի ձեռքբերումներին զուգընթաց պետք է նշել, որ ժամանակակից հասարակությունների արագ զարգացումը պահանջում է տեսական կառավարման մոդելների պարբերական վերանայում և համապատասխանեցում հասարակության ներկայիս կրթական կարիքներին: Կառավարման մոդելի ընտրության չափանիշների մշակման անհրաժեշտությունը պայամանվորված է կրթական համակարգի վերաբերյալ ժամանակակից սոցիալական պահանջներով և սպասելիքներով: Հանրակրթության կառավարման ոլորտում այսօր արդեն իսկ ի հայտ են եկել այնպիսի խնդիրներ, որոնցից առանձնահատուկ կարևորություն են ներկայացնում հետևյալ խնդիրները. - պրակտիկայում կառավարման տարբեր մոդելների առկայությունը և դրանց տեսական հիմնավորման բացակայությունը, - կրթական համակարգերի կառավարման մոդելների ֆորմալ ընտրությունը, - հակասությունները կրթական համակարգում բազմաթիվ փոփոխությունների ևայդ փոփոխությունները կառավարելու նպատակով մոդելների տեսամեթոդական հիմնավորվածության բացակայության միջև: Հանրակրթության կառավարման ոլորտում առկա խնդիրների լուծմանն ուղղված տեսական և գործնական առաջարկությունների ձևակերպման համար ուսումնասիրվել են կառավարման մոդելների ձևավորման միտումները և դրանց էական բնութագրերը: Այս հետազոտության նպատակներից ներառում են սոցիալական կապերի հիմնական բնութագրերի նկարագրությունը, որոնք կազմում են հանրակրթական դպրոցների և հասարակության միջև փոխհարաբերությունների հիմնական կոնֆիգուրացիաները, և տարբեր երկրների ժամանակակից դպրոցներում գերիշխող կառավարման մոդելների տիպաբանության կառուցումը: Այս նպատակները ձևավորվել են հանրակրթության կառավարման ոլորտում միջազգային փորձի համեմատական ուսումնասիրության արդյունքում ձեռք բերված որակական տվյալների հիման վրա:
Keywords: Economics; Management